Design of Real Time Monitoring Queue List and Android-Based Search for Nearest Ambulance at Rangkasbitung Hospital - Krisna, Widura; Zakariyah, Muhammad (Institut Teknologi Bisnis AAS Indonesia, 2024)
Information technology has now changed almost all agencies, both private and public, especially at Dr. Adjidarmo Hospital, some problems at Dr. Adjidarmo Hospital requires solutions. One of the problems that exists is the accumulation of queues because they still use a manual system and take a long time and difficulty for patients to find ambulance information.The use of technology to improve this system is the best solution that can be done using the ADDIE method. ADDIE stands for the five stages of the development process, namely Analysis, Design, Development, Implementation, and Evaluation. The idea to simplify patient bureaucracy can be done with the health service android application with the Ambulance feature. Patients can use smartphones as a medium to find information on the whereabouts of ambulances. Patients can also determine where the location point is by using Google Maps which can find where a place or location is located. For queuing systems use firebase as a data store